Perlindungan Hukum Terhadap Korban Kekerasan Dalam Rumah Tangga dalam Putusan Pengadilan Negeri Sebagai Implementasi Hak-Hak Korban - Hamidah Abdurrachman (Fakultas Hukum Universitas Islam Indonesia, 2010)
This research discusses the form of legal protection for domestic violence victim woman in court decision and how is the effort in realizing the legal protection for domestic violence victim woman in Indonesian criminal system This research is a normative juridical using statute approach and case approach. Data collection conducted by literary study and document study, observation, and interview. Analysis is conducted qualitatively to obtain proper conclusion from the observed problem. This research found that some judge decisions show the absent of legal protection for domestic violence victim, because judge still imposed the decision merely based on statement in Acts and only imposed punishment to the perpetrator.Key words : Legal protection, victim, domestic violence, state court judge’s decision